IMPLEMENTASI METODE QUANTUM TEACHING PADA KELAS PEMELIHARAAN KELISTRIKAN KENDARAAN RINGAN: SEBUAH STUDI TINDAKAN KELAS PADA SALAHSATU SEKOLAH VOKASI DI KARAWANG - Makmur, Makmur (Jurnal Pendidikan Dasar dan Sosial Humaniora, 2022)
This research aims to improve student learning outcomes in light vehicle electrical maintenance subjects using a gasoline injection fuel system through a quantum teaching model. The researcher utilised a classroom action research method to answer the research questions. The researcher employed research at one vocational school in Cikampek involving thirty-one students as research subjects. The researcher used observations and tests to untangle students’ abilities. This research shows that students learning outcomes are improved with an outstanding category